Cinnamomum cassia (L.) J.Presl Alleviates Allergic Responses in Asthmatic Mice via Suppression of MAPKs and MMP-9 - Lim, Je-Oh; Kim, Yun Hee; Lee, Ik Soo; Kim, Woong-Il; Lee, Se-Jin; Pak, So-Won; Shin, In-Sik; Kim, Taesoo (Frontiers in Pharmacology, 2022)
The prevalence of asthma is gradually increasing, and endangers human health. Many therapeutic agents have been developed to address this concern. Cinnamomum cassia (L.) J.Presl is a traditional herbal remedy in China, Japan, and Korea and used mainly to control common cold, cough, pneumonitis and fever in Donguibogam, a medical encyclopedia of Korea. Therefore, we investigated whether C. cassia (L.) J.Presl extract (CCE) confers protective effects on asthma model induced by ovalbumin (OVA). The animals were received intraperitoneal administration of OVA on day 1 and 14, and then subjected to OVA inhalation from day 21 to 23. They were orally treated CCE (30 and 100 mg/kg) from day 18 to 23. CCE administration decreased allergic responses, including airway hyperresponsiveness, eosinophilia, inflammatory cytokine production, and immunoglobulin E in OVA-exposed mice, along with the decline in inflammatory cell count and mucus secretion in respiratory tract. Additionally, CCE suppressed MAPK phosphorylation and MMP-9 expression in OVA-exposed mice. Overall, CCE treatment attenuated allergic responses induced by OVA exposure, which may be connected to the suppression of MAPK phosphorylation.